Economic Cost of Traceability in U.S. Beef Production - Shear, Hannah E.; Pendell, Dustin L. (Frontiers in Animal Science, 2020)
Livestock traceability has increasingly become a focus for the USDA, the National Cattlemen’s Beef Association, high-volume beef-exporting states, and other beef industry stakeholders. The focus on traceability within the United States (U.S.) began after several international animal disease outbreaks and continues to be of importance with highly infectious diseases spreading across the globe. Mitigating adverse future disease outbreaks and food safety events, as well as maintaining export markets through a positive international perception of U.S. beef has become a top priority. Implementing a national animal identification (ID) and traceability program would enable the industry to track and reduce the potential losses due to an outbreak or event. However, such a system comes at a cost, mainly to cow-calf producers. This study utilizes a partial equilibrium model to determine the impacts of a beef cattle animal ID and traceability system in the United States. Utilizing an economic model allows us to provide a comparison of how the various beef sectors would need to respond to offset the costs of a national animal ID and traceability program. Assuming no changes in domestic and international demand for U.S. beef, producers at the wholesale, slaughter, and feeder levels lose $475 million, $1,143 million, and $1,291 million, respectively, in a 10-year discounted cumulative producer surplus. A 17.7% and 1.9% increase in international and domestic beef demand would be required to completely offset the producer costs of CattleTrace, respectively.